MICHEL FOUCAULT: KUASA VERSUS RASIONALITAS MODERNIS (REVALUASI DIRI SECARA KONTINU) - Konrad Kebung (Institut Filsafat dan Teknologi Kreatif Ledalero, 2017)
This paper presents Michel Foucault’s thoughts on historical events in the past as they impact on the constitution of the self in the present. Thus, Foucault is known as an historian of the present. An expert in the history of the system of thought, he analyses how people thought and behaved throughout the history of philosophy from the Rennaisance to the classical period (17 th-18 in Foucault’s classification) and onto the 20thth century. As a postmodernist (and post-structuralist) thinker, he critiques modern rationality based mainly on the ego, subject, and consciousness, as passed down to present day thinking by René Descartes. He analyses critically this exclusive rationality and confronts it with his notion of discourse. This paper also presents ways of reading important historical events which were, and are, influential in human life in line with Foucault’s criticism. Keywords: Foucault, philosopy, discourse, subject, etict Artikel ini menyajikan pemikiran Michel tentang peristiwa sejarah masa lalu yang berguna bagi manusia pada masa sekarang. Foucault secara khusus dikenal sebagai sejarawan masa kini. Sebagai ahli dalam sejarah sistem pemikiran, Foucault menganalisis cara orang berpikir dan berperilaku sepanjang sejarah filsafat dimulai dari era Rennaisance, periode klasik (abad XVII-XVIII dalam klasifikasi Foucault), hingga abad XX. Sebagai pemikir posmodernis (dan postrukturalis), Foucault mengajukan kritik terhadap rasionalitas modern yang didasarkan atas ego, subjek, dan kesadaran, yang diwariskan sampai saat ini oleh René Descartes. Dia menganalisis secara kritis rasionalitas eksklusif ini dan menghadapkannya dengan gagasan wacana. Artikel ini juga menyajikan cara untuk membaca semua peristiwa sejarah yang penting dan berpengaruh terhadap kehidupan manusia sesuai dengan kritik Foucault. Kata-kata kunci: Foucault, filsafat , diskursus, subjek, etika